PENGGUNAAN METODE ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VI SD NEGERI 38 PADA PEMBELAJARAN IPS TENTANG DAMPAK GLOBALISASI - Ishak Said (CENDEKIAWAN, 2023)
ABSTRACT The background of the problem in this class action research is that students have not been active because the teacher still uses conventional methods in the form of lectures, so that the social studies learning outcomes of grade VI students of SD Negeri 38 Pangkalpinang have not yet reached the optimal completeness value. The problem is formulated as follows: "Does the use of Role Playing Learning Method can improve the learning outcomes of Social Studies on the Impact of Globalization on Grade VI students of SD Negeri 38 Pangkalpinang?". This type of research is Classroom Action Research (CAR). The CAR model uses 2 cycles, each cycle consisting of 4 stages namely 1) action planning, 2) action implementation and 3) observation, and 4) reflection. The subjects of the study were 23 grade students of SD Negeri 38 Pangkalpinang with 23 students. Data collection techniques are test techniques and observation techniques. The research instrument using item items and observation sheets. The analysis technique used is comparative descriptive which includes the comparison of mean, and percentage. The results of this study indicate an increase in students' social studies learning outcomes about the effects of globalization, after using the role playing learning method. This can be seen in the comparison of the average value ie in the pre-cycle conditions of 60, while in cycle 1 it increased to 65 and in cycle 2 it increased again to 70. The classical learning creativity scores in the pre-cycle conditions 55%; the first cycle increased to 75% and in the second cycle increased to 85%. Keywords: Method, Role Playing and Learning Outcomes